PERKEMBANGAN PERUMAHAN SKALA KECIL DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGANNYA DI KELURAHAN BUKIT LAMA PALEMBANG - Faradiah Hildy Putri (Jurnal Tekno Global, 2018)
Housing construction by private developers in Kelurahan Bukit Lama began in 1986 with the construction of Perumahan Poligon. Since then, housing construction continues in Kelurahan Bukit Lama. Residential housing is developed by private developers with the goal to the middle to the top. At the beginning, it is built a large-scale housing or housing that has numbers of units but this time more housing developments leading to small-scale housing. Small scale housing developments is seen in three aspects; growth, spatial, and actors. These three aspect are changed in different time unit. Small-scale residential development is influenced by factors of housing location. Housing location factors are seen from developer and buyer.Keywords: development, factors